(untitled) (Eurasian Medical Research Periodical, 2022)
The primary cause of cardiovascular disease and stroke is hypertension (HTN). However, it is rarely taken seriously and is frequently poorly managed. Lowering blood pressure (BP) lowers the hazards connected with it. The focus of hypertension therapy, as well as the debates over treatment paradigms, have shifted dramatically throughout time. Historically, the focus has been on identifying the best single-drug therapy for lowering the risk of cardiovascular disease